Microbial modulation of plant ethylene signaling: ecological and evolutionary consequences - Mohammadhossein Ravanbakhsh; Rashmi Sasidharan; Laurentius A. C. J. Voesenek; George A. Kowalchuk; Alexandre Jousset (Microbiome, 2018)
Abstract The plant hormone ethylene is one of the central regulators of plant development and stress resistance. Optimal ethylene signaling is essential for plant fitness and is under strong selection pressure. Plants upregulate ethylene production in response to stress, and this hormone triggers defense mechanisms. Due to the pleiotropic effects of ethylene, adjusting stress responses to maximize resistance, while minimizing costs, is a central determinant of plant fitness. Ethylene signaling is influenced by the plant-associated microbiome. We therefore argue that the regulation, physiology, and evolution of the ethylene signaling can best be viewed as the interactive result of plant genotype and associated microbiota. In this article, we summarize the current knowledge on ethylene signaling and recapitulate the multiple ways microorganisms interfere with it. We present ethylene signaling as a model system for holobiont-level evolution of plant phenotype: this cascade is tractable, extremely well studied from both a plant and a microbial perspective, and regulates fundamental components of plant life history. We finally discuss the potential impacts of ethylene modulation microorganisms on plant ecology and evolution. We assert that ethylene signaling cannot be fully appreciated without considering microbiota as integral regulatory actors, and we more generally suggest that plant ecophysiology and evolution can only be fully understood in the light of plant-microbiome interactions.